2008
DOI: 10.1186/1741-7007-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Hue-shifted monomeric variants of Clavulariacyan fluorescent protein: identification of the molecular determinants of color and applications in fluorescence imaging

Abstract: Background: In the 15 years that have passed since the cloning of Aequorea victoria green fluorescent protein (avGFP), the expanding set of fluorescent protein (FP) variants has become entrenched as an indispensable toolkit for cell biology research. One of the latest additions to the toolkit is monomeric teal FP (mTFP1), a bright and photostable FP derived from Clavularia cyan FP. To gain insight into the molecular basis for the blue-shifted fluorescence emission we undertook a mutagenesis-based study of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 36 publications
5
112
0
Order By: Relevance
“…rxRFP1.4 localized in the ER, as confirmed by colocalization studies with a previously established green fluorescent ER-mWasabi probe [19], responded to treatments of AT-2 (1 mM) and DTT (10 mM), demonstrating its usefulness as a fluorescent probe for redox dynamics in the ER (Figure 4A & 4B). We observed that the direct addition of DTT (10 mM) in the imaging medium was unable to fully reduce rxRFP1.4 in the ER, so we further developed a procedure to permeabilize cell membranes with digitonin.…”
Section: Invited Article For a Special Issue Featuring Young Investigsupporting
confidence: 69%
“…rxRFP1.4 localized in the ER, as confirmed by colocalization studies with a previously established green fluorescent ER-mWasabi probe [19], responded to treatments of AT-2 (1 mM) and DTT (10 mM), demonstrating its usefulness as a fluorescent probe for redox dynamics in the ER (Figure 4A & 4B). We observed that the direct addition of DTT (10 mM) in the imaging medium was unable to fully reduce rxRFP1.4 in the ER, so we further developed a procedure to permeabilize cell membranes with digitonin.…”
Section: Invited Article For a Special Issue Featuring Young Investigsupporting
confidence: 69%
“…In each round the brightest colonies were picked, plasmids isolated, and the pool of improved FP genes used as the template for the subsequent library. We have successfully applied this basic strategy to the optimization of a teal FP (27), blue FPs (17), and a YFP with violet excitation (37).…”
Section: Resultsmentioning
confidence: 99%
“…Brighter cyan FPs have recently been developed, such as Cerulean (Rizzo et al, 2004) or mTFP (Ai et al, 2008). Substitution of Cerulean for ECFP in cyan-to-yellow FRET sensors has improved SNR (Heim et al, 2007), though this may decrease photostability (Shaner et al, 2005).…”
Section: Practical Improvementsmentioning
confidence: 99%